Liposomal amphotericin B eradicates Candida albicans biofilm in a continuous catheter flow model - Seidler, Marc; Salvenmoser, Stefanie; Müller, Frank-Michael (FEMS yeast research, 2010)
The aim of this study was to test whether a Candida albicans biofilm can be eradicated by liposomal amphotericin B (LAMB) at the minimal inhibitory concentration in a novel catheter continuous flow model. After 24-h biofilm formation and a 24-h treatment with LAMB, the growth of the hyphal network was reduced to 20% in comparison with the untreated control, whereas fluconazole and caspofungin remained at an intermediate phase (50%). After 24-h biofilm formation and a 24-h treatment with LAMB, 20% of the surface was covered in biofilm and LAMB caused an uneven surface. For caspofungin and fluconazole, the surface covering was 80%. The extracellular matrix (ECM) of the infected, but untreated catheters had a thickness of 5-20 μm at 24 h and 10-150 μm at 48 h. After 24-h biofilm formation and a 24-h treatment with LAMB, the ECM was virtually cleared with 0 μm ECM. After 24-h biofilm formation and a 24-h treatment with fluconazole, the ECM thickness was comparable to the infected, but untreated catheter at 24 h with 10-25 μm; with caspofungin, the ECM thickness was comparable to the infected, but untreated catheter at 48 h with 10-130 μm. Comparing the blastospores, pseudohyphae and ECM, 0.5 μg mL−1 LAMB could eradicate Candida biofilm, whereas fluconazole and caspofungin were less effective.
Gesehen am 19.06.2023